2022
DOI: 10.1186/s13012-022-01211-w
|View full text |Cite|
|
Sign up to set email alerts
|

Primary aim results of a clustered SMART for developing a school-level, adaptive implementation strategy to support CBT delivery at high schools in Michigan

Abstract: Background Schools increasingly provide mental health services to students, but often lack access to implementation strategies to support school-based (and school professional [SP]) delivery of evidence-based practices. Given substantial heterogeneity in implementation barriers across schools, development of adaptive implementation strategies that guide which implementation strategies to provide to which schools and when may be necessary to support scale-up. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…In line with prior studies (Kilbourne et al, 2018;Smith et al, 2022), classroom teachers are currently being supported in the development of strategic thinking, leadership skills, and reduction of barriers related to tailored InPACT delivery through a five-step process. This process includes helping classroom teachers set measurable goals (e.g., reducing activity break transition times to increase instructional time), identifying teacher strengths to build self-efficacy, aligning tailored InPACT delivery with existing school and administrator values and priorities, providing guidance on overcoming school barriers to tailored InPACT delivery, and increasing engagement with administrators and other support staff.…”
Section: Implementation Facilitationmentioning
confidence: 85%
See 2 more Smart Citations
“…In line with prior studies (Kilbourne et al, 2018;Smith et al, 2022), classroom teachers are currently being supported in the development of strategic thinking, leadership skills, and reduction of barriers related to tailored InPACT delivery through a five-step process. This process includes helping classroom teachers set measurable goals (e.g., reducing activity break transition times to increase instructional time), identifying teacher strengths to build self-efficacy, aligning tailored InPACT delivery with existing school and administrator values and priorities, providing guidance on overcoming school barriers to tailored InPACT delivery, and increasing engagement with administrators and other support staff.…”
Section: Implementation Facilitationmentioning
confidence: 85%
“…Guided by the social learning and diffusion of innovations theories (Bandura, 1977;Rogers, 2003), enhanced REP is a multifaceted implementation strategy that bundles tailored program packaging and teacher training with implementation facilitation to provide schools with ongoing support (Kilbourne et al, 2014). Hence, enhanced REP addresses fundamental barriers to school-based intervention delivery and has been shown to improve the uptake of behavioral interventions in low-resource schools (Smith et al, 2022). We applied the enhanced REP framework to tailor InPACT program packaging, teacher training, technical assistance, and implementation facilitation processes to mitigate implementation barriers unique to low-resource schools .…”
Section: Overcoming Barriers Related To Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT is one mental health EBP with well-established evidence showing positive effects on youth with anxiety and depression ( Haugland et al, 2020 ; Higa-McMillan et al, 2016 ; Spirito et al, 2011 ), across racial groups ( Ginsburg & Drake, 2002 ; Rosselló & Bernal, 1999 ) and through modular or components-based programs ( Becker et al, 2012 ; Chiu et al, 2013 ). Studies have shown that CBT can be effectively delivered by SPs in school settings ( Ginsburg et al, 2020 ; Koschmann et al, 2019 ; Masia Warner et al, 2016 ; Sanchez et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that an incorrect version of Additional file 1 was published. The correct files are included in this Correction and the original article [ 1 ] has been updated.…”
mentioning
confidence: 99%